Allogeneic BK Virus-Specific T-Cell Treatment in 2 Patients With Progressive Multifocal Leukoencephalopathy. Issue 4 (July 2021) - Hopfner, Franziska; Möhn, Nora; Eiz-Vesper, Britta; Maecker-Kolhoff, Britta; Gottlieb, Jens; Blasczyk, Rainer; Mahmoudi, Nima; Pars, Kaweh; Adams, Ortwin; Stangel, Martin; Wattjes, Mike P.; Höglinger, Günter; et al.
Abstract : Objective: Progressive multifocal leukoencephalopathy (PML) is a devastating demyelinating opportunistic infection of the brain caused by the ubiquitously distributed JC polyomavirus. There are no established treatment options to stop or slow down disease progression. In 2018, a case series of 3 patients suggested the efficacy of allogeneic BK virus-specific T-cell (BKV-CTL) transplantation. Methods: Two patients, a bilaterally lung transplanted patient on continuous immunosuppressive medication since 17 years and a patient with dermatomyositis treated with glucocorticosteroids, developed definite PML according to AAN diagnostic criteria. We transplanted both patients with allogeneic BKV-CTL from partially human leukocyte antigen (HLA) compatible donors. Donor T cells had directly been produced from leukapheresis by the CliniMACS IFN-γ cytokine capture system. In contrast to the previous series, we identified suitable donors by HLA typing in a preexamined registry and administered 1 log level less cells. Results: Both patients' symptoms improved significantly within weeks. During the follow-up, a decrease in viral load in the CSF and a regression of the brain MRI changes occurred. The transfer seemed to induce endogenous BK and JC virus-specific T cells in the host. Conclusions: We demonstrate that this optimized allogeneic BKV-CTL treatment paradigm represents a promising, innovative therapeutic option for PML and should be investigated in larger, controlled clinical trials. Classification of Evidence: This study provides Class IV evidence that for patients with PML, allogeneic transplant of BKV-CTL improved symptoms, reduced MRI changes, and decreased viral load.